Artificial Intelligence in Islamic Higher Education Marketing: A SWOT Analysis from an Islamic Educational Management Perspective - Abdul Muin; Muhamad Afif; Fitri Hilmiyati; Aan Ansori; Wazin Wazin (Jurnal Pendidikan Islam, 2026)
The global digital transformation of higher education has accelerated the adoption of artificial intelligence (AI) in institutional marketing, yet its integration often prioritizes efficiency and competitiveness while overlooking educational values and ethical governance. This study aims to examine how AI-based marketing strategies can be optimized within Islamic higher education institutions through an Islamic Educational Management framework that aligns technological innovation with Islamic educational purposes. Employing a qualitative strategic analysis, the study utilizes Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), supported by a systematic literature review and secondary institutional data. The findings reveal that AI adoption offers significant strengths, including value-aligned personalization, improved administrative efficiency, and data-driven decision-making that supports the quality of educational services. However, internal challenges persist in the form of limited digital readiness and insufficient capacity for ethically grounded technology stewardship. Externally, growing demand for technology-enhanced Islamic education and supportive digitalization policies present opportunities, while competitive pressures and the need for Sharia-compliant digital governance pose substantial threats. The study concludes that AI-based marketing strategies, when embedded within Islamic Educational Management principles such as al-tadbir al-tarbawi and maqāṣid al-tarbiyah al-islāmiyyah, can strengthen institutional accountability, reinforce Islamic educational identity, and support sustainable transformation. These findings imply that Islamic higher education institutions should frame digital innovation as part of mission-driven educational reform rather than a purely managerial or promotional tool.